2008
DOI: 10.1089/ars.2007.1656
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Raises Cytosolic Calcium in Neurons Through Activation of L-Type Ca2+ Channels

Abstract: Hydrogen sulfide (H(2)S) concentration can be maintained in cell cultures within the range reported for rat brain by repetitive pulses of sodium hydrogen sulfide. Less than 2 h exposure to H(2)S concentrations within 50 and 120 microM (i.e., within the upper segment of the reported physiological range of H(2)S in rat brain), produces a large shift of the intracellular calcium homeostasis in cerebellar granule neurons (CGN) in culture, leading to a large and sustained increase of cytosolic calcium concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
93
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(100 citation statements)
references
References 35 publications
6
93
1
Order By: Relevance
“…This indicates that H 2 S promotes neuronal ACh release in a Ca 2ϩ -dependent manner. Similarly, previous studies have demonstrated that H 2 S raises ACh release in a Ca 2ϩ -dependent manner in type I glomus cells (31), in neurons (12,52), astrocytes (33), and microglia (29).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…This indicates that H 2 S promotes neuronal ACh release in a Ca 2ϩ -dependent manner. Similarly, previous studies have demonstrated that H 2 S raises ACh release in a Ca 2ϩ -dependent manner in type I glomus cells (31), in neurons (12,52), astrocytes (33), and microglia (29).…”
Section: Discussionsupporting
confidence: 71%
“…It has been suggested that H 2 S regulates Ca 2ϩ homeostasis in neuronal cells via activation of L-type Ca V channels, and thereby regulates the neurotransmitter release (12,27,52). In the central nervous system, H 2 S promotes synaptic release of glutamate (3).…”
mentioning
confidence: 99%
“…While short application (Ͻ15 min) of relatively low concentration of NaHS (Յ130 M) did not induce any current via NMDA receptor (20), overnight incubation with higher concentration of NaHS (200 -1000 M) alone caused neuronal death that is totally preventable by pretreatment with NMDAR antagonists (9). Our results may be in line with the latter study since we incubated primary cortical neurons with H 2 S donors for 24 h. On the other hand, H 2 S may activate other calcium channels and thereby indirectly activate NMDA receptors via releasing glutamate (21). Taken together, these observations support the hypothesis that cytotoxicity of H 2 S is at least in part mediated via enhancement of NMDAR activation.…”
Section: Discussionsupporting
confidence: 87%
“…This increased discharge is likely due to elevated levels of intracellular cytosolic calcium. It is well known that activity-dependent intracellular calcium overload may result in neuronal apoptosis (4,16,23). Thus, the possibility exists that one of the main functions of STC-1 within SFO is to reduce the influx and the rise in intracellular calcium levels (10, 70).…”
Section: Perspectives and Significancementioning
confidence: 99%